2021
DOI: 10.1002/ijc.33833
|View full text |Cite
|
Sign up to set email alerts
|

The unfavorable effects of COVID‐19 on Dutch advanced melanoma care

Abstract: The COVID‐19 pandemic had a severe impact on medical care. Our study aims to investigate the impact of COVID‐19 on advanced melanoma care in the Netherlands. We selected patients diagnosed with irresectable stage IIIc and IV melanoma during the first and second COVID‐19 wave and compared them with patients diagnosed within the same time frame in 2018 and 2019. Patients were divided into three geographical regions. We investigated baseline characteristics, time from diagnosis until start of systemic therapy and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 19 publications
1
12
0
1
Order By: Relevance
“…A recent study reported a significant delay in immunotherapy treatment of patients with advanced melanoma in the Netherlands. Moreover, a significant increase in brain metastases and worse performance status was found during the second lockdown 24 . While the increase in brain metastases may have resulted from improved screening instead of treatment delay, these results still suggest an unfavourable impact on patients with advanced melanoma care during the pandemic.…”
Section: Discussionmentioning
confidence: 96%
“…A recent study reported a significant delay in immunotherapy treatment of patients with advanced melanoma in the Netherlands. Moreover, a significant increase in brain metastases and worse performance status was found during the second lockdown 24 . While the increase in brain metastases may have resulted from improved screening instead of treatment delay, these results still suggest an unfavourable impact on patients with advanced melanoma care during the pandemic.…”
Section: Discussionmentioning
confidence: 96%
“…It has been reported that radical surgery and adjuvant therapy in patients with early‐stage cervical cancer can significantly increase patient survival, 31 while delayed diagnosis and treatment will affect patient prognosis 32 . Studies have predicted that delays in cancer diagnosis and treatment due to the COVID‐19 pandemic may affect clinical outcomes over the next decade 33 and have suggested that long‐term preventive measures to protect patients from COVID‐19 may increase cancer‐related mortality 34‐36 . Therefore, a series of measures should be taken to ensure cancer screening in public health emergencies, 26,37 such as allocating a sufficient number of healthcare workers; using risk stratification and classification to prioritize screening high‐risk women; using alternative cancer screening methods such as self‐sampling postal testing or establishing rapid diagnostic kits; after a short training period, allowing staff such as general practitioners, midwives or nurses to participate in screening programs.…”
Section: Discussionmentioning
confidence: 99%
“…In case of definitive SARS‐CoV‐2 infection, it is reasonable to suspend some targeted therapies like BRAF/MEK inhibitors and HHIs as they aggravate the course of SARS‐CoV‐2 infection and affect the outcome 15 . Anti‐PD‐1 courses are usually postponed in the settings of an acute infection due to the probability of COVID‐19 induced cytokine storm 33 . It is advised to delay cancer treatment for a short 2 to 6 weeks period or until clinical improvement 34 .…”
Section: Discussionmentioning
confidence: 99%